SAT0535 Eular 2018 core set of data to be collected in giant cell arteritis registries and databases viewpoints from a eular task force. (12th June 2018) - Ehlers, L.; Askling, J.; Bijlsma, J.W.; Cid, M.C.; Cutolo, M.; Dasgupta, B.; Dejaco, C.; Dixon, W.G.; Feltelius, N.; Finckh, A.; Gilbert, K.; Mackie, S.; et al.
Abstract : Background: Giant cell arteritis (GCA) represents the most common form of primary vasculitis and can be associated with severe and potentially life-threatening complications. Due to its low prevalence, systematically collected data on course and outcome of this disease are scarce. Objectives: The aim of this EULAR Task Force was to identify a core set of data items which can easily be collected from clinicians and facilitates examination of disease course and outcome. Methods: A multidisciplinary EULAR task force group of 20 experts including rheumatologists, epidemiologists and patient representatives was assembled and breakout groups formed for a meeting at which items from a previously compiled collection of core parameters for a GCA registry were evaluated. Results were presented to the other group members following a structured process for discussion and consensus finding. The meeting was followed by several rounds of discussions to achieve consensus. Results: A total of 95 items were identified, subdivided into the following categories: General, Demographics, GCA-related signs and symptoms, Other medical conditions, and Treatment. Suitable instruments and assessment intervals were determined for documentation of each item. To facilitate implementation of the recommendations in both primary care and scientifically oriented registers, a minimum core set of parameters was distilled, with supplemental items that can be added optionally depending on the designated purpose of individual registers. Conclusions: This core set intends to ensure that data from different GCA registries and databases can be compared for the dual purposes of clinical research and improving clinical care, thereby facilitating collaborative analyses. Disclosure of Interest: L. Ehlers: None declared, J. Askling Grant/research support from: Abbvie, BMS, MSD, Pfizer, Roche, Astra-Zeneca, Eli Lilly, Samsung Bioepis, UCB, J. Bijlsma Consultant for: Roche, SUN, M. Cid Consultant for: Roche, M. Cutolo Consultant for: Mundipharma, Horizon, B. Dasgupta Grant/research support from: Napp, Roche, Consultant for: Roche, Servier, GSK, Mundipharma, Pfizer, Merck, Sobi, Speakers bureau: UCB, Merck, C. Dejaco Grant/research support from: Pfizer, MSD, Consultant for: MSD, Pfizer, UCB, AbbVie, Roche, Novartis, Lilly, Celgene, Merck, Sandoz, GSK, W. Dixon Consultant for: Bayer, N. Feltelius Employee of: Swedish Medical Products Agency, A. Finckh Consultant for: AbbVie, AB2BIO, BMS, Eli-Lilly, MSD, Pfizer, Roche, K. Gilbert Consultant for: PMRGCAuk, S. Mackie Grant/research support from: Roche, GSK, Consultant for: Roche, Sanofi, Chugai, PMRGCAuk, A. Mahr Consultant for: Roche-Chugai, E. Matteson Grant/research support from: Novartis, Bristol Meyer Squibb, Hoffman-La Roche, Genentech, Consultant for: Glaxo-Smith-Kline, Endocyte, L. Neill Consultant for: PMR-GCA Scotland, C. Salvarani Consultant for: Roche, W. Schmidt Consultant for: Roche, GlaxoSmithKline, Sanofi, A. Strangfeld Speakers bureau: AbbVie, BMS, Lilly, MSD, Pfizer, Roche, Sanofi-Aventis, UCB, R. van Vollenhoven Grant/research support from: AbbVie, BMS, GSK, Pfizer, and UCB, Consultant for: AbbVie, AstraZeneca, Biotest, BMS, Celgene, Crescendo, GSK, Janssen, Lilly, Merck, Novartis, Pfizer, Roche, and UCB, F. Buttgereit Grant/research support from: Horizon Pharma, Consultant for: Horizon Pharma, Mundipharma, Roche, Galapagos